The impact of the use of new technologies on farmers’ wheat yield in Ethiopia: Evidence from a randomized control trial - Abate, Gashaw T.; Bernard, Tanguy; de Brauw, Alan; Minot, Nicholas (2017)
This study examines the impact of the Wheat Initiative technology package promoted by the research and extension systems in Ethiopia on wheat growers in the highlands of the country. The package includes certified wheat seed, a lower seeding density, row planting, fertilizer recommendations, and marketing assistance. A sample of 490 wheat growers was randomly assigned to one of three groups: the fullpackage intervention group, a marketing-assistance-only group, and a control group. The results suggest that the full-package farmers had around 14 percent higher yields after controlling for the type of farmer and household characteristics. Implementation of the Wheat Initiative was successful in terms of making certified seed and fertilizer accessible and increasing uptake, though only 61 percent of the intervention group adopted row planting and few farmers received marketing assistance. The measured yield difference may underestimate the true yield difference associated with the technology because of incomplete adoption of the recommended practices by intervention farmers and adoption of some practices by control farmers.